Identifikasi Penyebab Kecelakaan Kerja Konstruksi Menggunakan Accident Root Cause Tracing Model (ARCTM) dan Fault Tree Analysis (FTA) - Utami Dewi Arman; Jihan Melasari; Aldan Roby Suwanda (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2022)
The construction sector greatly contributed to the increase in the number of injuries and even deaths of workers. This study aims to identify unsafe conditions and unsafe acts and to analyze the causes of work accidents on the Talago Embung Project in the village of Sikabu kabu, Luhak, District of Limo Puluh Kota by using the Accident Root Cause Tracing Model (ARCTM) and Fault Tree Analysis (FTA). Data were collected through observation, in-depth interviews, and documentation. The causes of construction accidents identified are as follows; a) environmental factors i.e. weather or climate, lack of lighting, b) tools and facilities factors i.e. equipment life cycle, availability of Personnel Protective Equipment (PPE), and negligence in maintaining it, c) human factors i.e. personal issues, work pressure, and physical condition of workers, lack of skills and experience of workers, and d) management factors i.e. ineffective communication between the management team and workers and among workers, inadequate SOP and inappropriate material layout planning. Based on the results, it is expected that there will be training directly related to tasks and work safety, adequate project layout planning, proper supervision, and adequate maintenance of work safety equipment.